2008
DOI: 10.1007/s00467-007-0689-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo mesna and amifostine do not prevent chloroacetaldehyde nephrotoxicity in vitro

Abstract: Chloroacetaldehyde (CAA) is the putative metabolite responsible for ifosfamide-induced nephrotoxicity. Whereas evidence suggests that sodium 2-mercaptoethanesulfonate (mesna) and amifostine protect renal cells against CAA toxicity in vitro, their efficacy in clinical studies is controversial. To better understand the discrepancy between in vivo and in vitro results, we combined the in vivo intraperitoneal administration of either saline or mesna (100 mg/kg) or amifostine (200 mg/kg) in rats and the in vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The introduction of sodium 2-mercaptoethanesulphonate (mesna) has virtually eliminated haemorrhagic cystitis. However, mesna has no preventive effect on the tubular toxicity of ifosfamide [ 9 , 10 ]. Ifosfamide-induced tubular toxicity can be associated with metabolic acidosis with a normal anion gap (hyperchloremic acidosis) due to Type 1 (distal) or, less frequently, Type 2 (proximal) RTA.…”
mentioning
confidence: 99%
“…The introduction of sodium 2-mercaptoethanesulphonate (mesna) has virtually eliminated haemorrhagic cystitis. However, mesna has no preventive effect on the tubular toxicity of ifosfamide [ 9 , 10 ]. Ifosfamide-induced tubular toxicity can be associated with metabolic acidosis with a normal anion gap (hyperchloremic acidosis) due to Type 1 (distal) or, less frequently, Type 2 (proximal) RTA.…”
mentioning
confidence: 99%
“…14 , 30 In the in‐vitro study, Yaseen et.al demonstrated that chloroacetaldehyde altered lactate metabolism in isolated proximal tubules, and treatment with mesna, did not alter glutathione levels in renal cells. 31 …”
Section: Discussionmentioning
confidence: 99%
“…Chloroacetaldehyde directly reacts with thiols groups, leading to a decrease in the levels of glutathione (GSH) in the tubular cells, and mediates its nephrotoxicity 14,30 . In the in‐vitro study, Yaseen et.al demonstrated that chloroacetaldehyde altered lactate metabolism in isolated proximal tubules, and treatment with mesna, did not alter glutathione levels in renal cells 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the uro-protective thiol compound “Mesna” (sodium 2-mercaptoethanesulfonate) has virtually eliminated urotoxicity associated with both cyclophosphamide and ifosfamide and allowed the use of higher and more frequent dosing. However, mesna has shown no preventive effect on the tubular toxicity of ifosfamide, which manifests in Fanconi syndrome [67,68]. This is likely due to insufficient delivery of mesna to the renal tubule, leading to failure to provide adequate protection of tubular glutathione from depletion by the metabolite(s) [69].…”
Section: Fanconi Syndromementioning
confidence: 99%